The Impact of Parents' Role on the Motivation and Achievement of Gifted Children with Special Needs: A Review - Marwan, Alatawi (Journal of Intellectual Disability - Diagnosis and Treatment, 2023)
Background: Some unusual children experience prolonged distracted stress or risk factors that prevent them from maximizing their potential without specific treatment or support. Therefore, it appears that studying parental motivation and its impact on gifted children is very important. Objectives: The primary goal of this paper is to determine the impact of parental involvement on the development and motivation—of gifted children with special needs education (double exceptional). The paper also indicates the impact of parental involvement on children's educational outcomes. Results: The findings of this paper indicate that parental involvement significantly influences the motivation of children with special needs in terms of their achievement in the arts and how much they affect the academic achievement of double-exceptional students related to various aspects of science and life. Conclusion: As we found that parents are the initiators of double-differentiation in their children, future studies could explore knowledge and awareness of double-differentiation in parents. But our study reading how parents came to know their children twice unusually is essential as a first step in assessing parental thinking.